The Evaluation of Illustrations Images in the Content of the Computer Book for the Second Intermediate Grade from the Point of View of the Teachers of the Subject (Journal Of Educational and Psychological Researches, 2022)
The research aims at evaluating the illustrations images and determining the availability of good image standards in the illustrations images of the content of the second intermediate stage computer's book for the academic year (2019-2020) as seen by computer teachers. The sample was randomly selected, (30) teachers who are actually teaching the subject in schools within the geographical area of the province of Baghdad (Karkh III). To achieve this goal, ten standards were identified: scientific accuracy, suitability for the level of students, image clarity, image freshness, quality of coloring, suitability of its location of the subject, Matching their content glimpsed, The subject matter is appropriate in terms of area, matching its title to its content, the quality of visas, to know the strengths and strengthening and reduce the severity of weaknesses or eliminated by making proposals to improve them. The results revealed that the illustrations images in the content of the second-grade computer book did not take into account the good image standards in balanced proportions, where the scientific accuracy was (80%), which is a very good evaluation, and the standard percentage is suitable for the level of students (52%)The standard of image clarity was (57.3%), which is an acceptable evaluation grade, the standard of modernity of the image (74%) was a good evaluation, and the percentage of the color quality criterion (68%) was an average evaluation and the appropriate standard of its location. The percentage of the subject (67%) and when compared to the agreed rate came with an average evaluation, while the criterion of conformity of its content to the contents of the subject has achieved a rate (75%), a good evaluation, while the criterion of suitability in terms of area achieved (55%) Acceptable evaluation, the criterion of conformity of its title to its content by (56%), i.e. the degree of acceptable evaluation, and the standard of quality of visas achieved (58%). to conclude, the researcher came out with a number of recommendations and suggestions.